Primary structure of the gene encoding the bifunctional dihydrofolate reductase-thymidylate synthase of Leishmania major. - Beverley, S M (1986)
We have determined the nucleotide sequence of the dihydrofolate reductase-thymidylate synthetase (DHFR-TS) gene of the protozoan parasite Leishmania major (dihydrofolate reductase, EC 1.5.1.3 and thymidylate synthase, EC 2.1.1.45). The DHFR-TS protein is encoded by a single 1560-base-pair open reading frame within genomic DNA, in contrast to vertebrate DHFRs or mouse and phage T4 TSs, which contain intervening sequences. Comparisons of the DHFR-TS sequence with DHFR and TS sequences of other organisms indicate that the order of enzymatic activities within the bifunctional polypeptide chain is DHFR followed by TS, the Leishmania bifunctional DHFR-TS evolved independently and not through a phage T4-related intermediate, and the rate of evolution of both the DHFR and TS domains has not detectably changed despite the acquisition of new functional properties by the bifunctional enzyme. The Leishmania gene is 86% G+C in the third codon position, in contrast to genes of the parasite Plasmodium falciparum, which exhibit an opposite bias toward A+T. The DHFR-TS locus is encoded within a region of DNA amplified in methotrexate-resistant lines, as previously proposed.